International Comparison in Opiate Prescribing for New Users in Primary Care using Electronic Medical Record Data. (2018) - Tamblyn, Robyn; Girard, Nadyne; Habib, Bettina; Dixon, William; Jani, Meghna; Bates, David; Haas, Jennifer
No abstract available